2017
DOI: 10.1371/journal.pone.0172586
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis subtyping and its association with intestinal parasites in children from different geographical regions of Colombia

Abstract: Blastocystis is a common enteric protist colonizing probably more than 1 billion people with a large variety of non-human hosts. Remarkable genetic diversity has been observed, leading to the subdivision of the genus into multiple subtypes (ST), some of which are exclusively found in non-human hosts. The aim of this study was to determine the distribution of Blastocystis STs/18S alleles in symptomatic (abdominal pain, anal pruritus, diarrhea, headache, nauseas and/or vomit) and asymptomatic children from nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 38 publications
7
80
1
10
Order By: Relevance
“…Some studies not conducted in Latin America have found a low prevalence of Blastocystis in scenarios where there are alterations in the microbiota (such as those that may occur in inflammatory disease or Crohn's disease) when compared with a healthy population [3,21]. In the case of Colombia, cases of coinfection of Blastocystis with other intestinal protists have been reported, and there has been suggested zoonotic transmission of some subtypes of Blastocystis [22,23].…”
Section: Frequencies Of Coinfection Suggest a Possible Adaptation Of mentioning
confidence: 99%
“…Some studies not conducted in Latin America have found a low prevalence of Blastocystis in scenarios where there are alterations in the microbiota (such as those that may occur in inflammatory disease or Crohn's disease) when compared with a healthy population [3,21]. In the case of Colombia, cases of coinfection of Blastocystis with other intestinal protists have been reported, and there has been suggested zoonotic transmission of some subtypes of Blastocystis [22,23].…”
Section: Frequencies Of Coinfection Suggest a Possible Adaptation Of mentioning
confidence: 99%
“…In America, there is a high prevalence of ST1 and ST2, in Australia, Europe, and South Eastern Asia -ST1 and ST3, and in Europe -ST4 [10]. A recent study from SouthAmerica showed the presence of ST4 in humans [47] and latter STs 1, 2 and 3 were detected as the most frequent [48]. People are colonized mainly by ST1 through ST4, containing over 90% of assessments; but depending on the regions and countries, infection by ST5 through ST9 is also detected [10,20].…”
Section: Pathogenicity Of Blastocystis Sp Is a Relationship Possiblementioning
confidence: 99%
“…Ramírez et al, 2017) in Colombia as only 0.8% were positive for both B. hominis and H. nana. On the contrary,(Licea et al, 2003) found that both B. hominis and H. nana were detected in 8%.…”
mentioning
confidence: 97%